Balancing Freedom of Expression and Authority in Democratic Islamic Education - Khalil, Mohammed Thoha; Saputro, Yanuar Mahendra (Universitas Muhammadiyah Surakarta, 2025)
Islamic education in Muslim-majority countries often grapples with the tension between promoting freedom of speech and maintaining respect for religious authority. This imbalance poses a significant challenge in developing a democratic educational environment that encourages critical thinking while preserving Islamic values. The purpose of this study is to explore how Islamic education can balance these two principles—freedom of speech and authority—within the context of Indonesia, where this issue is highly relevant due to diverse educational practices and cultural expectations. Using a qualitative approach with a case study design, data were collected through in-depth interviews, direct classroom observations, and document analysis across several Islamic schools representing different regions and educational models. The results indicate that while 65% of students feel they are given space to express opinions, significant limitations still exist, particularly in more conservative institutions. Teacher and religious authority remain dominant, often restricting discourse on sensitive topics. However, some schools have successfully implemented democratic strategies such as musyawarah (consultation), allowing greater student participation without compromising religious principles. The findings suggest that a balanced approach is achievable through inclusive teaching methods and policy reforms that support both student expression and religious guidance. This study implies that rethinking pedagogical strategies and investing in teacher training are essential for creating Islamic educational environments that are both democratic and faithful to Islamic teachings.